Perbandingan aktivitas antidiabetes ekstrak air dan etanol Muntingia calabura L Folium terhadap mencit jantan - Pangondian, Aswan; PS, Nurunnisa; Husein, Saddam; Umaya, Chindy; Athaillah, Athaillah; Chandra, Putra (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Muntingia calabura L is an Indonesian herbal plant known as kersen which has the ability to reduce blood sugar levels. M. Calabura has secondary metabolites, namely flavonoids, tannins, triterpenoids, saponins and polyphenols. This study aimed to compare the antidiabetic activities of water and ethanol extracts of M. calabura in male mice. In this study, M. calabura was extracted using the maceration method with 70% ethanol solvent (EEMC) and decoction of Kersen leaves (EDMC). Blood glucose levels were measured at intervals of 15, 30, 45, and 60 minutes using a glucometer after being induced by alloxan induction. Animals were divided into eight groups (positive group, negative group and EEMC group, and EDMC group with doses of 125, 250 and 500 mg/kg BW. The results of the investigation showed that the activity to reduce blood glucose levels during the interval time was significantly different compared to the negative group, and positive control was not significantly different compared to the EEMC 250 mg/kg BW and EDMC 500 mg/kg BW groups. The conclusion of this study was that the EEMC and EDMC groups had decreased blood glucose levels. EEMC 250mg/kg BW and EDMC 500 mg/kg BW groups showed comparable activity to the positive control.